The Effect of Brainstorming Technique as a Pre-Writing Activity on the Students’ Achievement in Writing Descriptive Text - Eva Rahmawati (Journal Corner of Education, Linguistics, and Literature, 2022)
The objective of this research was to find out the effect of brainstorming technique on the students’ writing achievement. The approach of the research was quantitative. The design was one group pre-test and post-test design. The population of the research was students of the first grade of SMAN 1 Pringsewu and the sample of the research was class X consisting of 33 students. The activities were started from administering pre-test, doing treatment, and administering post-test. The instruments used were writing tests. The data were analyzed by using Repeated Measure t-test. The result showed that there was a statistically significant difference of the students’ writing ability between the pre-test and the post-test with the significant level of 0.05. This suggests that brainstorming technique facilitates the students to improve their ability in writing skills.